Anti-NMDA receptor encephalitis with neurologic sequelae refractory to conservative therapy with complete response to adjuvant therapy - Aaron Nizam; Andrew W. Menzin; Jill S. Whyte (Elsevier, 2020)
Background: Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis has been described in increasing frequency in association with benign, mature ovarian teratoma. Affected patients typically present with paraneoplastic limbic encephalitis with flu-like symptoms followed by altered mental status, acute psychiatric symptoms, seizures and amnesia. These symptoms can rapidly progressive if not treated aggressively with surgical resection. Profound neurological symptoms may require immunotherapy. Case: We present a case of anti-NMDA receptor encephalitis associated with a malignant immature teratoma in which symptoms were refractory to surgical management and initial immunotherapy. A complete neurologic response was only seen after initiating adjuvant chemotherapy. Conclusion: Anti-NMDA receptor encephalitis has rarely been described with immature ovarian teratomas. In these cases, a complete response may not be observed until systemic chemotherapy is started.